Since 9z is a multiple of 3z, it is automatically the LCM.
4z + 2 + 5z - 3 = 9z - 1
The above expression simplifies to 2x-y+9z
2 + 14z = -8 + 9zSubtract 9z from each side:2 + 5z = -8Subtract 2 from each side:5z = -10Divide each side by 5:z = -2
9x + 3y + 5z - 5x + 4z - 7y = 4x - 4y + 9z
8x + 9z
9z-5z = 30+z 3z = 30 z = 10
9z+8 = 3z-10 9z-3z = -10-8 6z = -18 z = -3
3(3z + 4)
It is 20z-18 when simplified
The following steps lead you to the correct answer: 9z = 5z + 16 9z - 5z = 16 4z = 16 z = 4, thus the correct answer is z = 4
-y+9z-16y-25z= -y-19y+9z-25z= -20y-16z There you go, are you happy. p.s it was easy (im 13yr)
It's 9z-7. because: you do the 8 times z first (8z) then add the z, (9z), then minus 7. 9z-7
There is no equation (nor inequality) to be solved!
z2 + 9z + 18 = z2 + 6z + 3z + 18 = z(z+6) + 3(z+6) = (z+6)*(z+3)